A Halloween story too: Dave and Nightdash in Grimvale - Wurfel, Marlene (My University, 2018)
A sequel to Nightdash set in the used-to-be-spooky town of Grimvale. But now, the Candy Cane Committee has put Christmas lights EVERYWHERE. Will Nightdash and Dave the little Monster and his bat friend be able to save Halloween?
Keywords: storytelling; children's stories